2014
DOI: 10.1101/cshperspect.a008995
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Receptor Tyrosine Kinase Ligand Processing

Abstract: A primary mode of regulating receptor tyrosine kinase (RTK) signaling is to control access of ligand to its receptor. Many RTK ligands are synthesized as transmembrane proteins. Frequently, the active ligand must be released from the membrane by proteolysis before signaling can occur. Here, we discuss RTK ligand shedding and describe the proteases that catalyze it in flies and mammals. We focus principally on the control of EGF receptor ligand shedding, but also refer to ligands of other RTKs. Two prominent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 140 publications
(154 reference statements)
0
16
0
Order By: Relevance
“…Each contains an EGF-like domain that is responsible for receptor binding and activation, with a characteristic pattern of six spatially conserved cysteines (that form three intramolecular disulfides). The EGFR ligands are all produced as membrane-bound precursor proteins (Harris et al 2003) and are cleaved by cell-surface proteases to yield the active growth factor species as described by Adrain and Freeman (2014). Although defects in EGFR affect a wide range of processes, it remains unclear which ligands are responsible in which context-with a few exceptions (Fiske et al 2009).…”
Section: Erbb Receptors and Their Ligandsmentioning
confidence: 99%
“…Each contains an EGF-like domain that is responsible for receptor binding and activation, with a characteristic pattern of six spatially conserved cysteines (that form three intramolecular disulfides). The EGFR ligands are all produced as membrane-bound precursor proteins (Harris et al 2003) and are cleaved by cell-surface proteases to yield the active growth factor species as described by Adrain and Freeman (2014). Although defects in EGFR affect a wide range of processes, it remains unclear which ligands are responsible in which context-with a few exceptions (Fiske et al 2009).…”
Section: Erbb Receptors and Their Ligandsmentioning
confidence: 99%
“…Generally, upon ligand binding, RTKs undergo multiple proteolytic cleavages in a protease‐dependent manner . For example, members of at least ten RTK sub‐families undergo a series of secretase cleavages after activation to remove the extracellular domain followed by release of the intracellular domain from the cell membrane, a process that is also known as regulated intra‐membrane proteolysis .…”
Section: Generation Of Intracellular Rtk Fragmentsmentioning
confidence: 99%
“…EGF family ligands are initially produced as transmembrane precursors, but proteolysis by ADAM-17 or Rhomboidfamily proteases typically occurs in the juxtamembrane region to release the active EGF peptide for paracrine signaling (Sahin et al 2004;Adrain and Freeman 2014). The different splice isoforms of C. elegans LIN-3/EGF differ in the region that would be expected to confer protease specificity, so the different biological activities observed for these isoforms might reflect different availabilities of isoform-specific proteases.…”
Section: Varied Activities Of Different Lin-3/egf Isoformsmentioning
confidence: 99%
“…LIN-3 is the only EGFrelated ligand in C. elegans, but alternative splicing generates at least four LIN-3 protein isoforms (S, L, XL, and XXL) that differ in their extracellular juxtamembrane domains ( Figure 4, A and B) (Dutt et al 2004;Van Buskirk and Sternberg 2007;Gerstein et al 2010). These isoforms may differ in binding partners or in susceptibility to proteolytic cleavage (Dutt et al 2004), which typically releases the active EGF domain from the transmembrane precursor (Rose-John 2013; Adrain and Freeman 2014). Prior OE studies have revealed some functional differences among these LIN-3 isoforms (Dutt et al 2004;Van Buskirk and Sternberg 2007), but their individual expression patterns and requirements are not known.…”
Section: Lpr-1 Localizes To Both Intracellular and Apical Extracellulmentioning
confidence: 99%